Thermal inactivation of salmonella typhimurium in dalandan juice drink a model validation study - Tolosa, Cyrho Penasas (University of the Philippines Diliman, 2007)
ABSTRACT The thermal inactivations of Salmonella Typhimurium (NRRL 4420) and Salmonella Typhimurium (E1366) were studied in dalandan juice drink at 72°C. The results were used to validate the predictive mathematical model for the decimal reduction time of Salmonella Typhimurium (ATCC 1311). Based on the results NRRL 4420 was significantly (P<0.05) more heat resistant compared to E1366. The predicted D values were also found to be significantly (P<0.05) greater than the actual D values for both NRRL 4420 and E1366. Model performance indices were within the acceptable range and showed overestimation of the observed responses of the two bacterial strains. The model also showed a better performance in NRRL 4420 than in E1366. Graphical validation suggested a fail-safe D values for both NRRL 4420 and E1366, and may be used to establish the decimal reduction time of Salmonella Typhimurium NRRL 4420 and Salmonella Typhimurium E1366 in dalandan juice drink.